Tecnologias assistivas destinadas a melhora da marcha em indivíduos pós AVC: testagem de protótipo e evidência de intervenção - Galvão, Wagner Rodrigues (2023)
Stroke is the third leading cause of Disability-Adjusted Life Years world. Reduced walking speed and weight-bearing asymmetry are commonly observed in post-stroke individuals. Assistive technologies (AT) are devices designed to assist people with disabilities by promoting functional benefits, providing assistance and safety during daily tasks at home and in the community. To investigate the perceived use and effect of different ATs in improving gait after stroke, this dissertation was divided into two products: in the first product we conducted a systematic review with meta-analysis with the following research questions: Does FEST improve motor function and activity outcomes compared to no intervention or placebo in individuals after subacute stroke? Does FEST combined with exercise programs improve motor function and activity outcomes compared to exercise programs in individuals after subacute stroke? Does FEST improve motor function and activity outcomes compared to an exercise program in individuals after subacute stroke? The present study was conducted and described according to the recommendations of the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist. Searches were performed in MEDLINE (Ovid), Cochrane, EMBASE, LILACS and PEDro databases, with the descriptors related to "Stroke", "Electric Stimulation Therapy", "Cycling" and "Clinical trials". The methodological quality of the studies was evaluated by the PEDro scale and the quality of evidence by the GRADE (Grading of Recommendations Assessment, Development and Evaluation) system. Five studies with 187 participants in the early subacute stage were included in the review, indicating that FEST combined with exercise programs promotes relevant benefits in trunk control (MD nine points, 95% CI 0.36 to 17.64) and walking distance (MD 94.84 meters, 95% CI 39.63 to 150.05, I=0%). This systematic review provides low to moderate evidence that FEST promotes similar or superior benefits compared to exercise programs on motor function and activity in early subacute post-stroke individuals. The second product consisted of a qualitative study to test and develop a prototype baropodometric insoles to diagnose and treat weight-bearing asymmetry. The Participatory Design method was used to explore the potential user's experience regarding their perspectives, and the facilitators, barriers, and requirements for the new technology were obtained. Our results were divided into the prototype development and testing stages, from the involvement of the potential user in the Participatory Design method and the identification of facilitators, barriers, and requirements to be improved. The potential user had a positive experience during the testing of the barometric insoles, showing an ease of walking and a quick correction of the asymmetry of weight distribution. We conclude that baropodometric insoles can be a promising resource for the diagnosis and treatment of asymmetry of weight distribution in post-stroke individuals.